Insight into paraneoplastic vasculitis associated with adenocarcinoma colon on F18-FDG PET-CT - Ayesha Zubair; Ahmed Qureshyl; Aamna Hassan (Journal of the Pakistan Medical Association, 2024)
Paraneoplastic vasculitis is a rare entity usually seen in haematological malignancies. Its incidence is even more rarein solid tumours like breast, renal, colon and lung. F-18 FDG PET-CT is commonly used to differentiate betweenactive vasculitis and atherosclerosis in patients with large to medium vessel vasculitis. We present a case ofmoderately differentiated adenocarcinoma colon presenting for the assessment of with paraneoplastic vasculitis. Keywords: vasculitis, paraneoplastic syndrome, adenocarcinoma colon.